Rozwój obszarów wiejskich w kontekście zmian pierwotnego rynku drzewnego w Polsce - Adamowicz, Krzysztof (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The paper analyzes general principles of functioning of the primary market in Poland. An outline of the production potentials influencing the discussed market was presented. Major problems associated with the discussed subjects were analyzed in the context of economic subjects participating in the primary timber market taking into consideration its demand-supply specificity. The author made an attempt to present a general characterization of the timber market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 149-156